2008
DOI: 10.1038/gene.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

IL2RA and IL7RA genes confer susceptibility for multiple sclerosis in two independent European populations

Abstract: Multiple sclerosis (MS) is the most common chronic inflammatory neurologic disorder diagnosed in young adults and, due to its chronic course, is responsible for a substantial economic burden. MS is considered to be a multifactorial disease in which both genetic and environmental factors intervene. The well-established human leukocyte antigen (HLA) association does not completely explain the genetic impact on disease susceptibility. However, identification and validation of non-HLA-genes conferring susceptibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 32 publications
4
69
0
4
Order By: Relevance
“…Although rs12722489 was significantly associated with risk in a recent validation study conducted in over 600 Canadian MS families, 10 it showed only marginal association (P ¼ 0.065) with risk in a combined French and German sample. 8 We did not genotype rs1570538, which was associated with risk in Spanish MS patients. 9 Located in intron 6 of the RPL5 (ribosomal protein L5) gene on chromosome 1p22, rs6604026 was associated with the risk of MS (P ¼ 0.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Although rs12722489 was significantly associated with risk in a recent validation study conducted in over 600 Canadian MS families, 10 it showed only marginal association (P ¼ 0.065) with risk in a combined French and German sample. 8 We did not genotype rs1570538, which was associated with risk in Spanish MS patients. 9 Located in intron 6 of the RPL5 (ribosomal protein L5) gene on chromosome 1p22, rs6604026 was associated with the risk of MS (P ¼ 0.…”
Section: Resultsmentioning
confidence: 79%
“…Recently the International MS Genetics Consortium (IMSGC) published the first SNP-based GWAS for MS with the aim of identifying novel MS susceptibility genes, and a list of 17 SNPs in 13 different gene loci were reported as showing statistical evidence (P ¼ 6 Â 10 À3 to P ¼ 9 Â 10 À81 ) of association with disease susceptibility. 5 Replication studies have since been performed, and provide support for a causal link between variation in the interleukin 7 receptor (IL7R), [6][7][8] interleukin 2 receptor alpha (IL2RA, also known as CD25), [8][9][10] EV15 11 and disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…These loci (the first non-MHC loci that were definitely associated with MS risk) encoded genes involved in immune regulation: the interleukin-2 receptor (IL2Ra) and the interleukin-7 receptor (IL7Ra). Associations with MS susceptibility for both loci were subsequently validated in other populations (Matesanz et al, 2001;Gregory et al, 2007;Lundmark et al, 2007a, b;Rubio et al, 2008;Weber et al, 2008). This landmark achievement established, unquestionably, that genes outside the MHC contributed to MS susceptibility.…”
Section: Genome-wide Association Screenmentioning
confidence: 98%
“…5,6 Only recently, with analysis of very large cohorts, non-human leukocyte antigen MS genes are starting to be unambiguously identified. [7][8][9][10][11][12][13][14] Another important concept is the sharing of risk genes between inflammatory diseases, 15 as now demonstrated for type 1 diabetes and MS genes. 12 Therefore, cross-disciplinary genetics may be rewarding.…”
Section: Introductionmentioning
confidence: 99%